Managers' mindfulness concerning institutional obstacles and the survival of SMEs - Izabella Steinerowska-Streb (Journal of Business Economics and Management (JBEM), 2022)
The study aims to identify the relationship between managers' mindfulness concerning business obstacles in an institutional context and the survival of small and medium enterprises (SMEs). The investigation was based on the data gathered in Poland through two linked studies. A Kaplan and Meier (1958) nonparametric estimation analysis was used to verify the hypotheses. The study's findings show that SMEs with mindful managers, paying attention to the institutional business barriers, survive longer than the other SMEs. The study results also reveal that the probability of SMEs survival significantly increases when managers are aware that bureaucracy constitutes a barrier to their firms' development. By identifying new effects of managers' mindfulness, the study's outcomes support the theory of mindfulness and extend the knowledge on mindfulness in organizations. Moreover, the survey findings support the institutional theory concerning business and entrepreneurship.
Keywords: D23; M14; 650; mindfulness; organization; manager; survival; SME; small and medium firms